On the Ideology of the Renovationist Church Groups in the first half of the 1920s: the First All-Russian Congress of the “Union of Church Revival” in 1924 and its main Decisions - Kulpinov Sergey, Deacon (Вестник Свято-Филаретовского института)
The article is devoted to the formation and final formalization of the ideology of the “Union of Church Revival” in the context of the development of the Renovationist schism in the Russian Orthodox Church in the first half of the 1920s. The work examines the process of formation of the “Union of Church Revival” as an independent church grouping, the circumstances of its separation from the “Living Church” in 1922, as well as the joint actions of the leader of the “Union”, “metropolitan” Antonin (Granovsky) with representatives of other renovationist groups within the framework of collegial Higher Church administration in the context of the preparation and conduct of the Renovationist II Local Council at the end of 1922 — the first months of 1923. The reasons for the final rupture of the “metropolitan” Antonin with the main renovation in the summer of 1923 are indicated. The main attention is paid to the work of the first All-Russian Congress of the “Union of Church Revival” in 1924, the circumstances of its convocation and key resolutions. The composition of the congress is being investigated, as well as the course of its work. The greatest attention is paid to the adopted resolutions on the attitude towards other church groups, on liturgical reforms and on the political position of the “Union of Church Revival”. The article examines the attitude of this church grouping to the results of the Renovationist II Local Council and the revision of a number of its decisions in the context of its own ideological course. It is noted that by the middle of 1924, the Union of Church Revival finally expressed its rejection of the canonical reforms of the II Local Council, primarily related to the married “hierarchy”. The total rejection of this innovation led to the fact that even the Patriarchal Church of this group had a much softer attitude than the lobbying of the “married episcopate” of the “Living Church” and the Renovationist Holy Synod, which preserved this practice. At the same time, the Union of Church Revival defended numerous liturgical reforms. It is concluded that the ideology of this church grouping combined liturgical reformism with canonical conservatism.